Volunteer activities in Ukraine amidst the COVID-19 pandemic - Baidarova, Olha (Social work and education, 2021)
The COVID-19 pandemic has become a serious challenge for Ukrainian society and has affected all spheres of activity, including volunteer activities of citizens. This article presents the results of the research on the state and peculiarities of the implementation of volunteer activities under COVID-19 conditions in Ukraine. The research was carried out in February–June 2021 using methods of metaanalysis of statistical data, questionnaires, and content analysis. It was found that 60% of officially registered volunteer organizations stopped their activities or cannot be identified as actively working. Analysis and systematization of monitoring data provided by the Ukrainian Volunteer Service allowed us to identify 77 organizations of various types that actually work during the quarantine period and actively recruit volunteer resources. Formal and informal organizations that have public web pages with contact information for electronic listservs were interviewed by 35 people. It was found that under quarantine conditions, the activities of the organizations that engage volunteer resources changed for 54% of the respondents, but despite the difficulties that 80% of the organizations experience, they continue to work. Inability to organize activities that involve direct contact with the recipient of the service, or the need for additional consideration of personal protection and safety equipment, both for the recipients of services and for the providers (volunteers), were the key difficulties in organizing the work of volunteers. Among the main changes, volunteers noted the change in the forms of work, the transition to a remote format, in particular in the Internet space, a reduction in the number of volunteers involved and the impossibility of conducting some activities, with postponement of implementation for an unspecified amount of time. It is noteworthy that most of the respondents assessed the quarantine situation as a situation of opportunities rather than restrictions, specifically, they noted the emergence of new areas of activity, one of which is assistance in combating the spread of the disease and counteracting the effects of COVID-19.